Tiger's voyage / 3. - Houck, Colleen (Houck, Colleen. Tiger's curse series, 2011)
After their battle with the villainous Lokesh, Kelsey and the Indian princes Ren and Kishan return to India, where Kelsey learns that Ren has amnesia and five cunning dragons try to keep the trio from breaking the curse that binds them.